2013
DOI: 10.1111/jam.12294
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of majorEscherichia colireductases involved in aerobic nitro and azo reduction

Abstract: Aims: Escherichia coli is able to reduce azo compounds such as methyl red (MR) and nitro compounds such as 7-nitrocoumarin-3-carboxylic acid (7NCCA). The aim of this study was to clarify the specificity of the major E. coli reductases. Methods and Results: Enzymatic assays with pure enzymes obtained after cloning, overproduction and purification under native or denaturing conditions were performed on three enzymes: AzoR, NfsA and NfsB. Their dependence on putative cofactors such as flavin mononucleotide (FMN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…This result was also consistent with recent findings, which demonstrated the prominent role of E. coli AzoR-purified enzyme under aerobic conditions (Mercier et al 2013). The remarkably high rate of decolorization for B46 was found to be dependent on the amount of biomass and the concentration of dye.…”
Section: Discussionsupporting
confidence: 82%
“…This result was also consistent with recent findings, which demonstrated the prominent role of E. coli AzoR-purified enzyme under aerobic conditions (Mercier et al 2013). The remarkably high rate of decolorization for B46 was found to be dependent on the amount of biomass and the concentration of dye.…”
Section: Discussionsupporting
confidence: 82%
“…These results corroborate a previous study (7) and can probably be attributed to the oxygensensitive nitroreductase system, which becomes active in the absence of oxygen and hence compensates for the (partial) loss of activity of the oxygen-insensitive nitroreductase system (19,20). In addition, another study using single-and double-knockout E. coli mutants targeting nfsA and nfsB showed that, at low oxygen levels, the mutants were still able to reduce the nitro compound 7-nitrocoumarin-3-carboxylic acid (7NCCA), indicating that NfsA and NfsB are not required for nitroreduction under anaerobic growth conditions (21). In ST2747-an, mutations in nfsA or nfsB could not be detected, although a 2-fold MIC increase was observed.…”
Section: Discussionmentioning
confidence: 99%
“…FMN is tightly associated with NfsA and NfsB, where it serves as a mediator for electron transfer from NAD(P)H to various substrates for nitroreduction (24). En- zymatic assays with 7NCCA demonstrated that both nitroreductases were greatly dependent on FMN for nitroreduction to proceed (21). The 12-nucleotide deletion in ribE resulted in a four-amino acid loss (TKAG) in the active site of lumazine synthase, at positions 131 to 134 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…), which are the two major nitroreductases in E. coli MG1655. As E. coli azoreductase AzoR displays nitroreductase activity [6, 18], a similar BLAST protein search was also performed using AzoR as the reference protein (AAC74494.1. ).…”
Section: Methodsmentioning
confidence: 99%